Evaluation of N-alkyl isatins and indoles as acetylcholinesterase and butyrylcholinesterase inhibitors - Kaitlyn N. Alcorn; Isabelle A. Oberhauser; Matthew D. Politeski; Todd J. Eckroat (Taylor & Francis Group, 2024)
AbstractTwo series of N-alkyl isatins and N-alkyl indoles varying in size of the alkyl group were synthesised and evaluated for inhibition of acetylcholinesterase (AChE) and butyrylcholinesterase (BChE). Among the N-alkyl isatins 4a-j, the addition of the N-alkyl group improved inhibition potency towards AChE and BChE compared to isatin. Selectivity towards inhibition of BChE was observed, and the increase in size of the N-alkyl group positively correlated to improved inhibition potency. The most potent inhibitor for BChE was 4i (IC50 = 3.77 µM, 22-fold selectivity for BChE over AChE). N-alkyl indoles 5a-j showed similar inhibition of AChE, the most potent being 5g (IC50 = 35.0 µM), but 5a-j lost activity towards BChE. This suggests an important role of the 3-oxo group on isatin for BChE inhibition, and molecular docking of 4i with human BChE indicates a key hydrogen bond between this group and Ser198 and His438 of the BChE catalytic triad.